Determining factors of the Spring SPA image in Portugal - Adriano Barreto Ramos; Joaquim Antunes; Elisa Álen (Millenium)
Introduction: Mineral Spring SPA in Portugal (sometimes referred to as Thermal) is part of health and wellness tourism, and gained prominence as a therapeutic and relaxation alternative. The image of SPA resorts directly influences the attractiveness and competitiveness of destinations.